Pengaruh Persepsi Return, Persepsi Risiko, Dan Literasi Keuangan Syariah Terhadap Keputusan Berinvestasi Generasi Z Kota Jambi Pada Saham Syariah - Naswaa Hasyim; Lucky Enggrani Fitri; Aditya Pratama (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study aims to analyze the effect of perceived return, perceived risk, and Islamic financial literacy on the investment decisions of Generation Z in Jambi City regarding Islamic stocks. This study used a quantitative approach with purposive sampling. Data were collected through questionnaires and analyzed using PLS-SEM. The results show that perceived return and Islamic financial literacy have a positive and significant effect on investment decisions, while perceived risk has no significant effect.